Differential Reynolds Stress Modeling for Separating Flows in Industrial Aerodynamics - Eisfeld, Bernhard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents recent progress in the application of RANS turbulence models based on the Reynolds stress transport equations. A variety of models has been implemented by different groups into different flow solvers and applied to external as well as to turbomachinery flows. Comparisons between the models allow an assessment of their performance in different flow conditions. The results demonstrate the general applicability of differential Reynolds stress models to separating flows in industrial aerodynamics.
Application of a low Reynolds differential Reynolds stress model to a compressor cascade tip-leakage flow -- Application of Reynolds stress models to separated aerodynamic flows -- Separated flow prediction around a 6:1 prolate spheroid using Reynolds stress models -- Influence of pressure-strain closure of the prediction of separated flows -- Modeling of Reynolds-stress augmentation in shear layers with strongly curved velocity profiles.
Keywords: Fluid mechanics; Fluids; Engineering Fluid Dynamics; Fluid- and Aerodynamics